Pengembangan Karakter Peserta Didik Melalui Scientific Approach dalam Pembelajaran Pendidikan Agama Islam Berbasis Kurikulum 2013 (Sebuah Grounded Theory) - Jamin, Ahmad (Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri (IAIN) Kerinci, 2019)
Islamic Education in schools is currently considered to be less effective and efficient. In addition, learning orientation is cognitive oriented and has not been able to optimize affective aspects, especially psychomotor. Though the spirit and essence of learning Islamic Education both in schools and madrasas give birth to graduates who have good, skilled Islamic insights and knowledge and noble character. Therefore, to realize the learning process of effective and efficient Islamic Education, a breakthrough is needed using the scientific approach, which is based on the 2013 curriculum. In its application, the scientific approach is an inductive, empirical approach. requires the flow of rational thinking, critical and emphasizes empirical (sensory) truth, needs to be synergized / integrated with theological, intuitive (zawq) approaches and deductive and supranational revelations to achieve the learning objectives of Islamic Education, namely increasing faith and devotion and building noble character . This paper aims to describe the application of the scientific approach in the learning of 2013 curriculum-based Islamic Education to create graduates with character.